Sodium hypochlorite suscepibility of coliforms isolated from chlorinated water supplies in Gweru - Mupandaguta, Edison (Midlands Sate University, 2015)
A study was carried out to determine the prevalence and evaluate the susceptibility to sodium hypochlorite of chlorinated water coliforms in Gweru municipal water supplies. Municipal water samples were collected from ten randomly selected suburbs between February and April 2014 from which the residual chlorine and presence of coliforms was determined. Evaluations of the susceptibility of isolated coliforms to sodium hypochlorite were done at concentrations ranging from 0.05 mg l-1 to 0.3 mg l-1 for 0, 5 10, 15, 20, 25 and 30 minute time intervals. The free residual chlorine concentration of municipal water obtained for the ten suburbs ranged from 0.05 mg l-1 to 0.4 mg l-1 depending on the proximity of the suburb to Gwenhoro water treatment plant. The furthest suburbs, Woodlands and Harben Park had the least mean residual chlorine levels (0.05 mg l-1) while the closest suburb, Southdowns, had the highest mean residual chlorine level (0.4 mg l-1). Chlorinated water coliform bacteria were isolated from 1 out of 30 samples collected, giving a prevalence of 3.33%. It took between 25 to 30 minutes for all the isolated chlorinated water coliforms to be killed by 0.2 mg l-1 of sodium hypochlorite, 10 minutes by 0.25 mg l-1 and 5 minutes by 0.3 mg l-1. The sodium hypochlorite concentration of 0.3 mg l-1 was most effective at killing chlorinated water coliforms as it does so within the minimum exposure time. This study serves as a baseline foundation on which further studies can be built in order to provide the most suitable and effective guidelines on sodium hypochlorite water disinfection in the homes that use municipal water supplies.